Optic neuritis revealing Kikuchi–Fujimoto disease. (July 2014) - Bouquet, F; Maillart, E; Vignal, C; Battistella, M; Meignin, V; Galicier, L; Gout, O
Kikuchi–Fujimoto disease is a rare systemic disease with uncommon neurological involvement. We report the case of a 30-year-old Asian woman who presented a rapidly progressive loss of vision. Magnetic resonance imaging (MRI) of the optic nerve revealed an inflammation of the left optic nerve with chiasmatic involvement, without any encephalic or medullar lesion. Thoracic computed tomography scan showed bilateral axillary lymphadenopathy. Analysis of a biopsy of the axillary lymph node showed typical histological findings of Kikuchi–Fujimoto disease. There was no clinical or biological sign of associated systemic lupus erythematosus. The patient spontaneously recovered normal visual acuity in 4 weeks, with resolution of MRI abnormalities. No optic neuritis relapse or neurological event occurred in a 3-year follow-up. To our knowledge this is the first case of optic neuritis associated with Kikuchi–Fujimoto disease.